Digitalization of Legal Information Management in Primary Schools Based on the JDIH Application: Digitalisasi Manajemen Informasi Hukum Sekolah Dasar Berbasis Aplikasi JDIH - Saada, Rahmadian A.; Lapatta, Nouval Trezandy (Technomedia Journal, 2025)
The rapid development of science and technology in the education sector has prompted institutions like the elementary school to improve the efficiency and effectiveness of information and legal management. This study aims to develop a Legal Documentation and Information Network (JDIH) application to facilitate the publication of school regulations. The primary objective of this research is to create an application that simplifies the management of student and school information, ensuring compliance with educational laws, and fostering an adaptive educational environment. The research used the System Development Life Cycle (SDLC) methodology, utilizing the Waterfall Model approach, which includes planning, analysis, design, implementation, testing, and maintenance. Data was gathered through observation, interviews, and literature studies, ensuring comprehensive insights into the existing regulatory management practices at the school. The JDIH application was successfully developed and implemented at the elementary school. It improved the accessibility of school regulations, ensuring better legal compliance and enhancing transparency. Positive feedback was received from respondents, with an average satisfaction level of 83.3%. This study demonstrates the effectiveness of the JDIH application in streamlining regulatory management. It is expected that the application will be expanded to other schools, further improving the management of legal information and promoting a more transparent and efficient educational environment.